EFFECTIVENESS OF MULTIDISCIPLINARY TEAM MEMBERS IN A COMPLEX, HIGH-RISK, AND STRESSFUL CRITICAL CARE UNIT (CCU) - Mahaman Laouali Moussa; Hussain Ahmed Sofyani; Fatchima L. Moussa; Bander Hammad Alblowi; Yahia Ahmad Oqdi; Saleh Khallaf; Hamad S. ALHarbi; Ahmed Albarqi (Indonesian Journal for Health Sciences, 2020)
Background: Critical Care Unit (CCU) serves as the most complex unit of the health care sector. The performance of multi-disciplinary team members working in CCU is affected through various factors such as; ineffective leadership, lack of communication, inappropriate team structuring etc. This study aims to evaluate the performance effectiveness of multidisciplinary team members working in the complex, risky and stressful environment of the critical care unit of Alansar General Hospital (AGH). Methods: A descriptive correlational study design is used. Data were collected through a structured questionnaire provided to a sample of 56 nurses working in CCU. Results: Findings indicated that the team working in CCU face problems due to ineffective conflict handling. Competent leadership is effective in providing appropriate team structure. Also, communication between team members helps in making useful decisions by using the knowledge gained through team communication. Conclusion: Multidisciplinary teams must be provided effective training to promote quality communication, knowledge sharing, and proper team structuring to improve quality of health care.